Necessary Fictions: Responsibility in Contemporary Canadian Historical Fiction - Aspenlieder, Erin D. (My University, 2011)
This dissertation considers the use – both the function and the value – of history in nine contemporary Canadian historical novels: Steven Heighton's Afterlands (2005), Don Gillmor's Kanata (2009), Rudy Wiebe's A Discovery of Strangers (1995), Fred Stenson's The Trade (2000), Michael Crummey's River Thieves (2003), Lawrence Hill's The Book of Negroes (2007), Merilyn Simonds's The Holding (2005), Aimée Laberge's Where the River Narrows (2004) and Jane Urquhart's A Map of Glass (2006). It asks what responsibilities authors of historical novels hold to the past and to readers in the present. It argues for making a distinction between irresponsible and responsible historical fiction, a separation marked not by the strict adherence to “fact,” but rather by the acknowledgement of the continued effect of past actions and relationships on the present, specifically the present configuration of the nation called Canada. I also characterize responsible historical fiction as committed to the notion of “truth-to-meaning” and requiring an engaged and active reader.
Keywords: historical fiction; Canadian historical fiction; contemporary Canadian fiction; responsibility; reader responsibility; Literature in English, North America; Literature in English, North America